2017
DOI: 10.3233/jad-170557
|View full text |Cite
|
Sign up to set email alerts
|

SPARCL1 Accelerates Symptom Onset in Alzheimer’s Disease and Influences Brain Structure and Function During Aging

Abstract: We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer’s disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Moreover, SPARCL1/hevin has recently been shown to play a key role in glutamatergic synaptogenesis during development [31]. We have recently shown that polymorphic variation in the SPARCL1 gene is associated with several AD endophenotypes, including accelerated cognitive decline, faster brain atrophy and altered neuronal activity in several brain regions [32]. Taken together, our findings suggest that SPARCL1 and A2M may respond to neuronal injury in preclinical AD.…”
Section: A2m and Synaptic Failure In Adsupporting
confidence: 65%
“…Moreover, SPARCL1/hevin has recently been shown to play a key role in glutamatergic synaptogenesis during development [31]. We have recently shown that polymorphic variation in the SPARCL1 gene is associated with several AD endophenotypes, including accelerated cognitive decline, faster brain atrophy and altered neuronal activity in several brain regions [32]. Taken together, our findings suggest that SPARCL1 and A2M may respond to neuronal injury in preclinical AD.…”
Section: A2m and Synaptic Failure In Adsupporting
confidence: 65%
“…The hub proteins of JUP (102) and GD12 (103) bind to presenilin-1, a component of ␥-secretase. SPARC1 is a protein involved in synaptic maintenance and is associated with age-related changes in brain structure (104).…”
Section: Molecular and Cellular Proteomics 196 1021mentioning
confidence: 99%
“…For each cohort, we model the annual MMSE score as a longitudinal outcome, follow-up year as the independent variable and sex, age at enrollment, and education as the covariates, with a random intercept and random slope per subject using the lme4 R package (version 1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The derived cognitive trajectory for each individual in Banner and BLSA cohorts is listed in supplementary table 1.…”
Section: Personalized Cognitive Trajectorymentioning
confidence: 99%